Vulnerabilidade ao HIV/AIDS em idosos: um estudo comparado - Gurgel, Sandra Nagaumi (2014)
Introduction: A change in the profile of aids has been happening, demonstrating a new characterization of the disease, where the elderly becomes part of vulnerable groups . This phenomenon may be associated with noncompliance of condom use, difficulty in early medical diagnosis, lack of access to information specific to this population; taboos about sexuality in this age group and the denial of the risk of infection. Evidence of gaps in knowledge of the elderly in relation to aids encourages the development of researches based in Socials Representations Theory, which seeks to identify the problem from the perspective of the individual as an important theoretical approach in the implementation and effectiveness of practices health. Objectives: To understand the social representations of vulnerability to HIV/Aids constructed by elderly people living with and without the disease and explore the differentiation of these representations between these different groups of elderly. Methodology: This is a descriptive exploratory study involving 26 patients of both sexes, were divided into two groups , between May and August 2013, in two institutions in João Pessoa. A semistructured interview was used to collect data. The database was processed by Iramutec software version 0.6 and sociodemographic data in SPSS 19.0. Results: There was a prevalence of elderly (73.1%), retired (92.3%) and Catholics (73.1%). Five classes emerged from the textual analysis. Despite knowledge about the disease, the elderly associated transmission of the virus to vulnerable group of young, poor, gays, not realizing vulnerable and their representations of aids are carried by negative images and prejudices. Final considerations: It is expected that these results can provide a basis for the implementation of specific actions for this population, since there is a significant increase in disease among the elderly and they do not see themselves vulnerable to HIV/Aids .